AGILE MANUFACTURING:PARADIGMA STRATEGI MANUFAKTURING ABAD 21 - Prapti, Meniek Srining (JURNAL BISNIS STRATEGI, 2007)
Agile manufacturing, a recently popularized concept, has been advocated as the 21st century manufacturing paradigm. Markets become highly diversified and global, and continuous and unexpected change, become the key factors for success. The need for a method of rapidly and costÂ effectively developing products, production facilities, and supporting information technology has led to the concept of agile manufacturing. Agile manufacturing requires enriching of the customer, cooperating with competitor organizing to manage change, uncertainty and complexity; and leverage people and information. The key enabler of agile manufacturing include: i) virtual enterprises formation, ii) physically distributed teams, iii) integrated business information system. This framework as a basis for understanding the major strategies and relevant tecnnologies of agile manufacturing (AM).